SANCACO COFFEE SYINBIOTIC (PROBIOTIC AND PREBIOTIC) AND ANTIBACTERIAL ASSAY AGAINST Escherichia coli - Miksusanti, Miksusanti; Adik Ahmadi; Syndi N.K; Dasril Basir; Heni Yohandini K (Pusat riset dan Inovasi Nasional, 2023)
Robusta coffee is one of the plants used as a drink and has an efficacious content that can be modified to be used as a cure for diarrhea. This research was conducted To determine the effect of synbiotic coffee with a combination of coffee, prebiotic inulin chicory, probiotic B. bifidum, and glucose on the growth and antibacterial activity of the probiotic Bifidobacterium bifidum BRL-130. Organoleptic testing of synbiotic coffee was performed on 30 panelists, then the growth test used the total plate count method, and the antibacterial test used the paper diffusion method. The organoleptic test showed that the selected formula 1 had the highest average taste of 3.76. In the symbiotic coffee growth test, the best results were obtained in week 1 of plain water with a temperature of 40°C with the number of colonies 5.95 x108 CFU/mL. Antibacterial activity test using paper disc diffusion method with a variation of the selected formula 1 treatment control, 2 treatment control pure robusta coffee powder, positive control of ciprofloxacin antibiotic, and negative control of aquadest solvent. The antibacterial activity of synbiotic coffee against E. coli showed that there was an inhibitory response in formula 1 against Escherichia coli bacteria in the first week of storage, 12.3±1.1 mm with strong criteria.